Biophysical studies of m2glyr modified sequences: The effect of electrostatics on ion channel selectivity - Bukovnik, Urska (Kansas State University, 2011)
Channel replacement therapy represents a new treatment modality that could augment existing therapies against cystic fibrosis. It is based on designing synthetic channel-forming peptides (CFPs) with desirable selectivity, high ion transport rates and overall ability to supersede defective endogenous chloride channels. We derived synthetic CFPs from a peptide initially reconstituted from the second transmembrane segment of the α-subunit of Glycine receptor (M2GlyR). Our best candidate peptide NK4-M2GlyR T19R, S22W (p22-T19R, S22W) is soluble in aqueous solutions, has the ability to deliver itself to the epithelial cell membranes without the use of a delivery system, is non-immunogenic, but when assembled into a pore, lacks the structural properties for anion selectivity. Previous findings suggested that threonine residues at positions 13, 17 and 20 line the pore of assembled p22-T19R, S22W and recent studies indicated that an introduction of positively charged 2, 3-diaminopropionic acid (Dap) at either T13 or T17 in the sequence increases transepithelial ion transport rates across the apical membranes of Madin-Darby canine kidney (MDCK) epithelial cells. This study focused on further structural modifications of the pore-lining interface of p22-T19R, S22W assembled pore. It was hypothesized that singly, doubly or triply introduced Dap residues modify the pore geometry and that their positively charged side chains impact discrimination for anions. Dap-substituted p22-T19R, S22W peptides retain the α-helical secondary structure characteristic for their parent p22-T19R, S22W. The sequences containing multiple Dap-substituted residues induce higher short circuit current across the epithelial MDCK cells compared to peptides with single Dap-substitutions or no Dap-substitutions. Whole-cell voltage clamp recordings using Xenopus oocytes indicate that Dap-substituted peptide assemblies induce higher levels of voltage-dependent but non-selective ion current relative to p22-T19R, S22W. Studies using the D-enantiomer of p22-T19R, S22W and shorter truncated sequences of a full length L-p22-T19R, S22W and L-Dap-substituted peptides provided evidence that peptide-induced ion transport rates can be attributed to formation of de novo pathways. Results of preliminary computer modeling studies indicate that Dap residues affect the pore geometry but not ion selectivity. Future studies focusing on modifying the existing electrostatic environment towards anion selectivity will focus on staggering the charged residues of Dap at various locations inside synthetic pores.
Keywords: Synthetic channel-forming peptides; Cystic fibrosis; Ion channel selectivity; Biochemistry (0487)